PENINGKATAN PEMAHAMAN SOAL CERITA MATERI PENJUMLAHAN DAN PENGURANGAN DENGAN MODEL PBL BERBANTUAN AUDIO VISUAL UNTUK SISWA KELAS 2 SDN KLIWONAN - Purba Muhammad Sidiq; Ahmad Solehudin; Hendry Wahyu Nugroho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In addition and subtraction material in mathematics subjects in grade 2, students still experience difficulties, especially in understanding word problems. Therefore, a learning method or model is needed that can help overcome students' problems or difficulties in learning. One solution that can be done to overcome this problem is the application of the PBL learning model with audio-visual assistance. This research aims to increase understanding of addition and subtraction story problems for grade 2 students at SD N Kliwonan. This research uses a classroom action research method with 2 cycles. The subjects of this research were 32 grade 2 students at SDN Kliwonan, Purworejo District. There were 2 cycles of action in this research (Cycle I and Cycle II). The data collection techniques used in this research are interviews, observation, tests and documentation. The results of the research show that: 1) The application of the problem based learning model in understanding addition and subtraction word problems was carried out in 2 cycles with different results. In Cycle I, the results of observing student activities were 81% (very good). Meanwhile, in Cycle II there was an increase, the results of observing student activities were 84% (very good). 2) Increased understanding of addition and subtraction story problems for class 2 students at SDN Kliwonan in Cycle I, the class average was 81 (very good) which reached a minimum performance indicator of 80. In Cycle II there was an increase in the class average, namely 84 (very good). The percentage of student learning completeness increased from Cycle I 81% to 84% in Cycle II with an increase of 3%